2017
DOI: 10.1002/eat.22737
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of avoidant/restrictive food intake disorder in a cohort of young patients in a partial hospitalization program for eating disorders

Abstract: Our findings suggest that patients with ARFID can be successfully treated in the same PHP as patients with other ED, with comparable improvements in weight and psychopathology over a shorter time period. Results are limited to patients with ARFID who exhibit an acute onset of severe food restriction. Future research should incorporate measures relevant to the diagnosis of ARFID and explore how patients with different ARFID subtypes may respond to various treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
114
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(122 citation statements)
references
References 33 publications
7
114
1
Order By: Relevance
“…As noted previously (Ornstein et al, ), our PHP tends to treat patients who exhibit an acute onset of food restriction resulting in significant weight loss or failure to gain weight. Thus, our results may not generalize to other subtypes of patients with ARFID, or patients treated in settings other than a PHP.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…As noted previously (Ornstein et al, ), our PHP tends to treat patients who exhibit an acute onset of food restriction resulting in significant weight loss or failure to gain weight. Thus, our results may not generalize to other subtypes of patients with ARFID, or patients treated in settings other than a PHP.…”
Section: Discussionmentioning
confidence: 83%
“…When hospitalized for medical stabilization, patients with ARFID had longer stays than those with AN; however, there was no difference in remission and readmission rates one year after discharge (Strandjord, Sieke, Richmond, & Rome, ). We previously reported on a cohort of patients in a partial hospitalization program (PHP) for ED and found similar improvements in weight from intake to discharge in those with ARFID and AN, with a shorter length of stay for patients with ARFID relative to those with other ED (Ornstein, Essayli, Nicely, Masciulli, & Lane‐Loney, ).…”
Section: Introductionmentioning
confidence: 90%
“…These studies have generally not compared ARFID/selective eating samples with samples representing other eating and feeding disorders. However, compared to patients with other eating disorders, ARFID patients have been reported to score significantly lower on the Children's Eating Attitudes Test (Nicely et al, ; Ornstein et al, ) and on all subscales of the Eating Attitudes Test and the Eating Disorder Inventory (Nakai et al, ). Notably, a couple of these studies (Ellis, Galloway, Webb, & Martz, ; Zickgraf & Ellis, ) utilize the highly opaque convenience samples of Amazon's Mechanical Turk web panel, the validity of which has, as seen above, been questioned (Landers & Behrend, ).…”
Section: Resultsmentioning
confidence: 99%
“…These emerging data suggest that ARFID may be as common as AN and BN. Further, studies from North America have shown that 5–12% of patients presenting for eating disorder care at outpatient clinics (911) and 22.5–24.6% of patients presenting to an outpatient day program for younger adolescents with eating disorders (12,13) meet DSM-5 criteria for ARFID.…”
Section: What Is Known About Arfid?mentioning
confidence: 99%
“…In some patients, it can be difficult to ascertain in a single evaluation whether the patient has ARFID or AN, and the close observation of an eating disorder program can provide diagnostic clarification. One study demonstrated that patients with ARFID could be successfully treated at eating disorder day treatment programs, demonstrating weight gain, decreased food restriction, and decreased anxiety symptoms (13). …”
Section: Treatmentmentioning
confidence: 99%